Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Pelanggan Indihome: (Studi PT Telkomsel di Kota Cirebon) - Novitasari, Febby; Silvianita, Anita (eProceedings of Management, 2024)
In the telecommunications sector, ensuring high levels of customer satisfaction is essential for sustainable businessgrowth. This research focuses on investigating how service quality and product quality influence customer satisfactionwithin IndiHome, a prominent telecommunications provider managed by PT Telkomsel in Cirebon City, Indonesia.The study aims to evaluate how customers perceive IndiHome's service and product quality, measure their overallsatisfaction, and explore the impact of service and product quality on customer happiness. A survey involving 384respondents aged 34 to 39, predominantly entrepreneurs, was conducted to gather data on their perceptions. Thesurvey, designed to assess service quality, product quality, and satisfaction levels, employed a quantitative approachwith descriptive analysis. Sampling was non-probabilistic and purposive, and data was collected via questionnairedistribution. The findings reveal that both service and product quality significantly influence customer satisfaction,suggesting that addressing these aspects can enhance competitiveness and customer retention in thetelecommunications market. This study offers valuable insights for telecom firms seeking to improve service deliveryand achieve sustained business success by meeting customer expectations effectively. Keywords-telecommunications, service quality, product quality